A abordagem constitucional e a atividade registral aplicada à regularização fundiária urbana para a obtenção do direito à moradia - Salgado, Suzana Valle (2023)
This dissertation will carry out an approach, in view of the promulgation of Law No. 13,465, of July 11, 2017 - which provides for the rural and urban land regularization in Brazil, among other inherent issues to the topic - through academic research, about how these policies public land trusts tend to simplify the property allocation process, in irregular settlements in urban areas, more specifically in Municipality of São Valentim, RS, with occupations in the area consolidated, exempting the beneficiary from having title to the asset with the maintaining environmental sustainability. Through the analysis of generational reasons for the law, the object of this research, aims to demonstrate that the normative scope has the purpose of seeking the regularization of irreversible land situations, which are inoperative with the Brazilian legal system. Land Regularization aims to essential, the realization of the right to housing, and it must be highlighted that the said right must be accompanied by essential requirements for it to become an effective policy, in which the existence of minimum conditions that allow for physical structuring, the existence of a habitable environment and the concrete possibility of proper regularization of access to the urban area. Therefore, it is clear that the right to housing, embodied in Law no. 13.465/17, does not become an end in itself, there being a pressing need checking conditions inserted in a context that allows access to all services and equipment necessary for citizenship. The present work falls within the PPGD/UPF line of research regarding Jurisdiction Constitutional and Democracy.